Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.4 - The Chain Rule - 3.4 Exercises - Page 204: 36



Work Step by Step

$y=x^{2}e^{-1/x}$ Differentiate using the product rule: $y'=(x^{2})(e^{-1/x})'+(e^{-1/x})(x^{2})'=...$ Use the chain rule to find $(e^{-1/x})'$: $...=(x^{2})[(e^{-1/x})(-\dfrac{1}{x})']+(e^{-1/x})(2x)=...$ Write $-\dfrac{1}{x}$ as $-x^{-1}$ and continue with the differentiation process: $...=(x^{2})[(e^{-1/x})(-x^{-1})']+(e^{-1/x})(2x)=...$ $...=(x^{2})[(e^{-1/x})(x^{-2})]+(e^{-1/x})(2x)=...$ Simplify: $...=e^{-1/x}+2xe^{-1/x}=e^{-1/x}(1+2x)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.